Solution-grown GeO2 nanoparticles with a nearly 100% yield as lithium-ion battery anodes. Issue 101 (17th October 2016) - Li, Guo-An; Li, Wei-Chin; Chang, Wei-Chung; Tuan, Hsing-Yu
Abstract : Germanium oxide (GeO2 ) nanoparticles were synthesized with a nearly 100% production yield in a nonionic reverse micelle system at ambient temperature as high performance lithium-ion battery anodes. Abstract : Germanium oxide (GeO2 ) nanoparticles were synthesized with a nearly 100% production yield in a nonionic reverse micelle system at ambient temperature. The procedure is a facile and energy saving strategy for producing germanium oxide nanoparticles with ultra large throughput. As-prepared GeO2 nanoparticles can be directly used as anode materials without any post-treatment or other supplementary additives for lithium ion batteries. GeO2 -anodes exhibited good electrochemical performance in terms of both gravimetric and volumetric capacity. The GeO2 anodes have a reversible capacity of approximately 1050 mA h g −1 at a rate of 0.1C, close to its theoretical capacity (1100 mA h g −1 ), and good rate capability without severe capacity decade. The volumetric capacity of the GeO2 anodes reaches 660 mA h cm −3, which is higher than the performance of commercial graphite anode (370–500 mA h cm −3 ). Coin type and pouch type full cells assembled for electronic devices applications were also demonstrated. A single battery is shown to power LED array over 120 bulbs with a driving current of 650 mA. Based on the above, the micelle process of GeO2 nanoparticle synthesis provides a possible solution to high-capacity nanoparticles' scalable manufacturing for lithium ion battery applications.